2020
DOI: 10.3390/ma13235584
|View full text |Cite
|
Sign up to set email alerts
|

Selective Laser Melting and Electron Beam Melting of Ti6Al4V for Orthopedic Applications: A Comparative Study on the Applied Building Direction

Abstract: The 3D printing process offers several advantages to the medical industry by producing complex and bespoke devices that accurately reproduce customized patient geometries. Despite the recent developments that strongly enhanced the dominance of additive manufacturing (AM) techniques over conventional methods, processes need to be continually optimized and controlled to obtain implants that can fulfill all the requirements of the surgical procedure and the anatomical district of interest. The best outcomes of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 71 publications
3
54
0
1
Order By: Relevance
“…On the other hand, the unlimited freedom in geometrical shapes and complexity of printed objects allows these technologies to compete with reasonably, or even overtake, traditional ones [4]. For a long time, the development and wider use of AM technologies have been limited by the poor selection of printing materials, which were mostly polymers; however, currently, it can be used for a very wide range of materials from thermoplastics to metals [5,6], ceramics [7][8][9], and biocompatible [10] or composite materials [11,12]. Composite materials, especially reinforced materials using continuous carbon fibre, have been recently introduced to additive manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the unlimited freedom in geometrical shapes and complexity of printed objects allows these technologies to compete with reasonably, or even overtake, traditional ones [4]. For a long time, the development and wider use of AM technologies have been limited by the poor selection of printing materials, which were mostly polymers; however, currently, it can be used for a very wide range of materials from thermoplastics to metals [5,6], ceramics [7][8][9], and biocompatible [10] or composite materials [11,12]. Composite materials, especially reinforced materials using continuous carbon fibre, have been recently introduced to additive manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization of the inclination angle facilitates the rapid fabrication and functionalization of implants in a single-step process, without postprocessing or with only local processing. Ginestra et al [64] found that the inclination angle has a limited effect on surface topography, highlighting the influence of different AM processing techniques on surface properties. It is not a simple task to explore the influence of a single parameter on antibacterial properties, and further in vitro and in vivo studies are required to this end.…”
Section: The Effect Of Am Technology On Antimicrobial Propertiesmentioning
confidence: 99%
“…Larger pore sizes are associated with higher compressive modulus [ 35 ]. The potential of gradient porosity scaffolds to preserve and restore their elastic properties after deformation is their key advantage, while square pores help to increase the stable mechanical strength [ 36 ].…”
Section: Introductionmentioning
confidence: 99%